Carbon footprint and cost–effectiveness of cataract surgery. Issue 1 (January 2016) - Venkatesh, Rengaraj; van Landingham, Suzanne W.; Khodifad, Ashish M.; Haripriya, Aravind; Thiel, Cassandra L.; Ramulu, Pradeep; Robin, Alan L.
Abstract : Purpose of review: This article raises awareness about the cost–effectiveness and carbon footprint of various cataract surgery techniques, comparing their relative carbon emissions and expenses: manual small-incision cataract surgery (MSICS), phacoemulsification, and femtosecond laser-assisted cataract surgery. Recent findings: As the most commonly performed surgical procedure worldwide, cataract surgery contributes significantly to global climate change. The carbon footprint of a single phacoemulsification cataract surgery is estimated to be comparable to that of a typical person's life for 1 week. Phacoemulsification has been estimated to be between 1.4 and 4.7 times more expensive than MSICS; however, given the lower degree of postoperative astigmatism and other potential complications, phacoemulsification may still be preferable to MSICS in relatively resource-rich settings requiring high levels of visual function. Limited data are currently available regarding the environmental and financial impact of femtosecond laser-assisted cataract surgery; however, in its current form, it appears to be the least cost-effective option. Summary: Cataract surgery has a high value to patients. The relative environmental impact and cost of different types of cataract surgery should be considered as this treatment becomes even more broadly available globally and as new technologies are developed and implemented.